Strategies For Overcoming Challenges In The Integration Of Religious Education In Public Schools: A Study Of The Role And Dynamics Of Stakeholders In The School Entry Program - Iman Subasman; Faat Nasyiruddin (Jurnal Ilmu Sosial Mamangan, 2024)
The importance of religious-based character education in the formal education system has become the attention of researchers to find the right model. This research identified the main problems in the implementation of the Ajengan Entering School (AMS) program, namely resistance from public school teachers and obstacles to curriculum integration. The research investigates how local government efforts overcome the challenges of implementing the AMS program. The aim of this research is to obtain effective strategies and identify obstacles in the implementation of AMS, using a qualitative research approach through in-depth interviews and document analysis. The findings show that collaboration between key stakeholders plays an important role in the successful integration of religious education in public schools, even though it is faced with significant challenges related to curriculum adaptation and social acceptance. The main conclusion is that the effectiveness of the AMS relies heavily on strategic communication and policy adaptation that is responsive to the needs and diversity of stakeholder views. The implications of this research are mainly related to the formulation of educational policies that are more inclusive and adaptive to the religious context in Indonesia.